Analisis dan Evaluasi Tingkat Kepuasan Pengguna Learning Management System Menggunakan Metode PIECES Framework - Raden Sumantri; Rofi Taufiqurrohman (JSAI (Journal Scientific and Applied Informatics), 2024)
This study aims to analyze and evaluate the level of user satisfaction with the Learning Management System (LMS) using the PIECES Framework method. LMS has become a crucial component of modern education, facilitating the management of learning content and interaction between teachers and learners. Evaluation of user satisfaction with LMS is very important to ensure its effectiveness in supporting the learning process. The PIECES Framework method is used as a foundation to analyze five main dimensions, namely Performance, Integration, Economy, Control, Efficiency, and Security of the LMS. The study collected data through surveys, interviews, and observations to gain comprehensive insights into user experience. The subjects of this study were teachers and students at SMK Maarif NU 2 Ajibarang. This research uses a questionnaire using the PIECES Framework method. The analysis results use the class interval formula and the mean formula. This measurement is taken from indicators of questionnaire questions which are grouped as very bad or poor. The results prove that the quality of the LMS at SMK Maarif NU 2 Ajibarang is good, bad, very bad, very good and fair. The results of this research will be presented to the management of Maarif NU 2 Ajibarang Vocational School. After conducting research, it was seen that the LMS of SMK NU 2 Maarif had good quality according to the PIECES Framework standards